2020
DOI: 10.1080/20013078.2020.1785161
|View full text |Cite
|
Sign up to set email alerts
|

Exosome therapeutics for lung regenerative medicine

Abstract: Exosomes are 30 to 100 nm extracellular vesicles that are secreted by many cell types. Initially viewed as cellular garbage with no biological functions, exosomes are now recognized for their therapeutic potential and used in regenerative medicine. Cell-derived exosomes are released into almost all biological fluids, making them abundant and accessible vesicles for a variety of diseases. These naturally occurring nanoparticles have a wide range of applications including drug delivery and regenerative medicine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 81 publications
0
68
0
Order By: Relevance
“…Exosomes have proven to be stable, biocompatible modalities to deliver a specific protein, miRNA or drug (Popowski et al., 2020) and represents a valuable tool to deliver therapies to tissue in otherwise difficult to treat diseases such as CF. Our previous study demonstrated the exosome mediated delivery of modified antisense oligonucleotides into nasal epithelial cells with the F508del mutation, which corrected the CFTR function (Villamizar et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes have proven to be stable, biocompatible modalities to deliver a specific protein, miRNA or drug (Popowski et al., 2020) and represents a valuable tool to deliver therapies to tissue in otherwise difficult to treat diseases such as CF. Our previous study demonstrated the exosome mediated delivery of modified antisense oligonucleotides into nasal epithelial cells with the F508del mutation, which corrected the CFTR function (Villamizar et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as the investigation of EV cargo advances into the identification of defined factors, new platforms, and strategies for enhancing EV bioactivity and improving therapeutic potency continue to be developed. Indeed, many reports of therapeutic EVs have identified therapeutically relevant cargo that triggers tissue healing and repair through attenuation of inflammation and fibrosis, promotion of tissue protection, repair, and angiogenesis [ 34 , 112 ]. Many of these defined factors include miRNAs, other small RNAs, and proteins [ 95 , 102 ].…”
Section: Therapeutic Roles Of Extracellular Vesiclesmentioning
confidence: 99%
“…The physiologic and pathogenic roles of EVs suggests their utility as a therapeutic platform in the restoration of organ homeostasis and reversal of tissue damage. Indeed, the steady migration of cells to EV therapy in regenerative medicine is primarily due to the versatility of these particles over traditional cell transplantation therapy [ 22 , 33 , 34 , 35 ]. The advancement of EV cargo content engineering renders EVs more versatile and customizable to several disease types [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be noted that many of these trials are limited in numbers of participants, scope and detailed data availability. Many commercial companies have also pursued EVs as therapeutics (Popowski et al., 2020).…”
Section: Why Are Evs Advantageous As Therapeutics?mentioning
confidence: 99%